Numerical analysis of leading edge cylinder aerofoil on Selig S1223 for moving surface boundary control - Mohammad Ali, Hidayatullah; Mohd Rafie, Azmin Shakrine; Md Ali, Syaril Azrad (Aeronautical and Astronautical Society of the Republic of China, 2021)
The Leading Edge Cylinder Aerofoil has resulted in an outpour of research studies for almost a century till date but fewer attempt has focused on the embedment of a cylinder with undercambered aerofoil. This research was aimed to ascertain whether the concept could enhance the intended aerofoil’s aerodynamic properties. The performance of the model was tested using computational fluid dynamic code ANSYS Workbench 2019 to simulate two-dimensional flow analysis with a variant of rotational speed up to 2000 RPM for different free stream speeds ranging from 5 to 30 m/s at various angles of attacks with the Reynolds number ranged from 4.56E+05 to 2.74E+06. The mesh independency test has been validated with an error of less than 1% prior to designing the best model embedment. The analysis resulted in an enhancement in the lift coefficient and stall angle delay of about 23% and 61%, respectively.